The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/03630242.2014.896442
|View full text |Cite
|
Sign up to set email alerts
|

Stories of Postpartum Depression: Exploring Health Constructs and Help-Seeking in Mothers’ Talk

Abstract: This article explores behavioral constructs derived from the Integrative Model of Behavioral Prediction (Fishbein, 2009) that emerged from unsolicited, online stories from 30 mothers about their experiences with postpartum depression. Five constructs (i.e., social norms; severity; barriers to help-seeking; facilitators to, and cues to action for, help-seeking; and self-efficacy) were prevalent and were connected with help-seeking behaviors in the stories that were analyzed after a single data collection in Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 17 publications
0
53
0
Order By: Relevance
“…These reviews reported themes of unmet expectations of motherhood, shame, guilt, and extreme vulnerability. Women experience stigma associated with mental health difficulties as well as the implication that PPD signals failure as a mother . One meta‐synthesis of women's experiences of severe mental health difficulties highlighted the importance of being a mother in these women's experiences.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These reviews reported themes of unmet expectations of motherhood, shame, guilt, and extreme vulnerability. Women experience stigma associated with mental health difficulties as well as the implication that PPD signals failure as a mother . One meta‐synthesis of women's experiences of severe mental health difficulties highlighted the importance of being a mother in these women's experiences.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been few attempts to synthesize these data. Understanding the therapy process and motivation to engage may be important in designing interventions which facilitate help‐seeking …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 The intensive mothering message in treatment guidelines 6 and self-help books insists that motherhood should bring happiness and, when it does not, medical intervention is necessary. 7 In stories 8 and interviews 9 women express feelings of failure to meet perceived standards of what a mother should be.…”
Section: Stigma Intensive Mothering and Essentialismmentioning
confidence: 99%